2013
DOI: 10.1155/2013/428363
|View full text |Cite
|
Sign up to set email alerts
|

Use of Radiofrequency Ablation in Benign Thyroid Nodules: A Literature Review and Updates

Abstract: Successful thermal ablation using radiofrequency has been reported in various tumors including liver or kidney tumors. Nonsurgical minimally invasive ablative therapy such as radiofrequency ablation (RFA) has been reported to be a safe and efficient treatment option in managing symptomatic cold thyroid nodules or hyperfunctioning thyroid nodules. Pressure and cosmetic symptoms have been shown to be significantly improved both in the short and long terms after RFA. For hyperfunctioning thyroid nodules, RFA is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 61 publications
1
39
0
2
Order By: Relevance
“…Non-surgical treatment options were used to treat benign thyroid nodules. Those modalities have achieved great efficacy and mild complications [3,5,6,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical treatment options were used to treat benign thyroid nodules. Those modalities have achieved great efficacy and mild complications [3,5,6,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported series of LA usually included patients with larger thyroid nodules and the series of RFA included patients with a higher cyst component [2]. Thus, the results are difficult to be compared [28]. To date, only one review including meta-analysis [29] and a more recent paper on a small case series [30] have reported direct comparisons between the two techniques with contradictory conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported improvements in neck discomfort and aesthetic symptoms after thyroid RFA. In the literature, aesthetic issues have been assessed by means of a score (generally from 1 to 4 or from 0 to 3) [12]. In our study, we used The aesthetic scale of ThyPRO, which did not reveal any improvement after thyroid RFA.…”
Section: Discussionmentioning
confidence: 99%